Strategy for Developing Horticultural Agrotourism Potential in Nagari Aie Angek, X Koto District, Tanah Datar Regency, West Sumatra (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This study aims to examine the strategy of the potential development of horticultural crop agrotourism in Kenagarian Aie Angek, X koto District, Tanah Datar Regency. The method used in this study is a descriptive approach, for the analysis of the study is to use SWOT analysis which seeks to find out various internal and external factors from a study studied. From the research that has been carried out and the results of the analysis show that the strategy of horticultural crop development in Nagari Aie Angek, X Koto District, especially farmers who absorb horticultural crops, experience various obstacles such as disruption of horticultural crops from pests and diseases and uncertain climate. However, UPTD Aie Angek horticultural crops continue to strive to cultivate the potential of horticultural agrotourism with various efforts and designs on how horticultural crops can ensure the economy of the community in Aie Angek District, X Koto District, Tanah Datar Regency